PTU-003 Gastroscopy Consent Training For Foundation Doctors: A Novel Teaching Strategy. (9th June 2014) - Chilkunda, DS; Beal, H; Khiyar, Y
Abstract : Introduction: Postgraduate Medical Education and Training Board (PMETB), now part of General Medical Council, reports on Foundation Schools have highlighted lack of consent training among Foundation Year 1 doctors (FY1s). 1 This can impact on patient safety and misguide expectations, thus adversely affecting patient experience. It could also affect FY1s' confidence as they often feel they obtain consent for procedures without adequate training. Robust consenting skills are integral to good medical practice and require urgent attention. Hence we developed a new teaching programme on consenting for diagnostic gastroscopy (DG), which is the commonest inpatient procedure undertaken in the endoscopy unit, and as this procedure is less complex with relatively rare serious complications. Methods: We initiated an apprenticeship model of training for consenting as part of mandatory FY1 induction. To facilitate this, we designed a formal assessment tool called Direct Observation of Gastroscopy Consent Taking Skills (DOGCTS). We developed a three-stage process. Stage 1: FY1s were provided small group teaching on consent and procedure. Stage 2: FY1s chose from available list of training slots, which were published after liaison between Endoscopy Unit and East Riding Medical Education Centre. Stage 3: FY1s observed one consenting process and DG by experienced endoscopist and underwent formal assessment using DOGCTS tool. Results: This pioneering programme was introduced to all FY1s working in Medicine and Surgery in HRI starting in August 2012. Since its inception, 139 FYs have been trained with 100% attendance rate. In order to avoid disruption to lists, only one FY1 was trained per list. Programme allowed FY1s to plan training around their clinical commitments. Successful completion of DOGCTS has been integrated into FY portfolio-requirements. Feedback from FYs has been positive and they have reported improved confidence. Patients have informally expressed that they had a better patient experience. Conclusion: Development of such a novel apprenticeship model allows for trainees and trainers to interact in an open, inclusive and non-threatening manner. It provides FY1s flexibility to manage their learning needs and trainers a chance to give formative feedback in real-time. Such a dynamic approach can not only improve confidence of FY1s but also instil public confidence in healthcare training. It has provided an excellent training opportunity in addition to being useful evidence for training-portfolios. It also caters to quality assurance and medico-legal aspects (pertaining to consenting) for NHS Trusts. We aim to undertake a formal survey of patient satisfaction annually and roll out this programme for flexible sigmoidoscopy consent as well. Reference: 1PMETB Report on Quality Assurance of FY1 programme visit to London deanery 2009 Disclosure of Interest: None Declared.